A Review Paper on Biodegradable Composites Made from Banana Fibers - Pannu, Amrinder Singh; Singh, Sehijpal; Dhawan, Vikas (Asian Journal of Engineering and Applied Technology, 2018)
Composites are defined as mixture of two or more ingredients where one is called as matrix (larger in quantity) and other is called reinforcement (smaller in quantity). Now a days research is concentrated towards various methods of making biodegradable composites where either reinforcement or matrix are biodegradable or both are biodegradable. Composites have so many applications in industrial as well as commercial use due to their low weight to strength ratio that attracted the automobile manufacturers to use these materials in cars which in turn increases the efficiency as well as reduce the cost of the automobile. In this paper effort has been made to investigate various process of manufacturing composites manufactured from banana fibers using different matrix preferably PLA (Polylactic Acid). The methods of improving the bonding between the reinforcement and matrix, effect of fiber orientation, size of the fibers and percentage reinforcement has been studied.